Comparative Study to Assess the Effectiveness of Transabdominal Preperitoneal Procedure and Open Lichtenstein Repair of Inguinal Hernias in Term of Postoperative Pain and Duration of Hospital Stay - Saeed, Rehan; Khattak, Abubaker; Sarwar, Saeed; Khan, Muhammad Amin; Aamir, Muhammad; Khan, Ahmad Yar (Indus Journal of Bioscience Research, 2025)
Background: Inguinal hernias are common surgical conditions that can have a tremendous effect on the quality of life for patients. The selection of the surgical approach can affect the postoperative pain and convalescence. The present paper compares the result of the Transabdominal Preperitoneal (TAPP) procedure and the Open Lichtenstein repair with respect to the postoperative pain and the length of the hospital stay. Objective: To compare the mean postoperative pain score and mean hospital stay with open Lichtenstein repair and transabdominal preperitoneal procedure in patients with inguinal hernia. Study Design: Randomized controlled trial. Duration and Place of Study: The study was conducted from January 1, 2024, to July 5, 2024, in the Department of Surgery at KTH Peshawar. Methodology: Sixty male patients ranging in age from 18 to 60 years with diagnosed inguinal hernias were randomized into a group of 30 patients for each group. The Visual Analog Scale (VAS) was applied for the pain assessment four hours after the surgery and the duration of the hospital stay was recorded. Results: The mean pain score was significantly lower in the TAPP group (4.63 ± 0.99) compared to the Open Lichtenstein group (6.40 ± 1.24), yielding a t-value of 6.068 and a p-value of 0.000. However, both groups had comparable hospital stay durations: 36.03 hours for the Open Lichtenstein repair and 36.90 hours for the TAPP procedure, with a t-value of -0.342 and a p-value of 0.734. Conclusion: The Transabdominal Preperitoneal procedure significantly reduces postoperative pain compared to the Open Lichtenstein repair for inguinal hernias.